Synthesis, biological and theoretical properties of crystal zinc complex with thiosemicarbazone of glyoxylic acid - Huseynova, Mansura; Farzaliyev, Vaqif; Medjidov, Ajdar; Aliyeva, Mahizar; Ozdemir, Mucahit; Taslimi, Parham; Zorlu, Yunus (Elsevier, 2022)
A new zinc complex with thiosemicarbazone of glyoxylic acid (1) was synthesized with zinc acetate dihy-drate and thiosemicarbazone of glyoxylic acid and crystallized in water. The absolute crystal structure of the complex was defined using the single-crystal X-ray diffraction technique. It was seen in X-ray mea-surements that the complex crystallized in the triclinic system with the P-1 space group. The structure of 1 represents distorted octahedral geometry around the central zinc metal. Zn(II) complex with thiosemi-carbazone of glyoxylic acid was an inhibitor of acetylcholinesterase (AChE), butyrylcholinesterase (BChE), human carbonic anhydrase I and II isoforms (hCA I and II) receptors and the inhibitor constant (Ki) values of the synthesized complex were 38.94 +/- 8.2 mu M for hCA I, 48.62 +/- 11.3 mu M for hCA II, 65.16 +/- 11.4 mu M for BChE and 82.04 +/- 16.0 mu M for AChE, respectively. The molecular docking method was used to show the complex-enzyme interactions. The pharmacokinetic properties of the complex were determined by ADME/Tox predictions and the results obtained showed that the complex could be a potential drug can-didate. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Thiosemicarbazones; Synthesis; Crystal structure; Enzyme inhibition; Theoretical calculations